Endovascular repair of an abdominal aortic aneurysm using bifurcated stent-graft in a patient with bilateral external iliac artery occlusion - Nabulsi, Bilal; Bianchini Massoni, Claudio; Tecchio, Tiziano; Ucci, Alessandro; Rossi, Giulia; Perini, Paolo; Azzarone, Matteo; De Troia, Alessandro; Freyrie, Antonio (Acta Biomedica Atenei Parmensis, 2019)
Abdominal aortic aneurysm (AAA) in association with external iliac artery (EIA) occlusion is a rare entity which may limit endovascular aortic aneurysm repair (EVAR) feasibility. We describe the case of an 84-year-old man affected by a 64mm infrarenal inflammatory abdominal aortic aneurysm with complete bilateral occlusion of EIA and patency of both common and internal iliac arteries. The common femoral arteries (CFA) were patent, and the patient was asymptomatic for lower limb claudication. The treatment was performed by EVAR using a bifurcated stent-graft after the recanalization of the left EIA, achieving technical success.